Development of solid state terahertz interferometer for the first plasma on HL-2M tokamak - Shi, P. W.; Yang, Z. C.; Shi, Z. B.; Xu, L. F.; Deng, W. C.; Jiang, M.; Chen, W.; Zhong, W. L.; Wen, J.; Fang, K. R.; Tong, R. H.; Xue, G. Q.; et al. (Review of scientific instruments, 2021)
A solid state terahertz interferometer has been developed on the recent commissioned HL-2M tokamak. It can work in a wide frequency region of 220–325 GHz, and the terahertz wave is generated from a low frequency phase locked voltage controlled oscillator with the frequency multiplying technique. A phase processor based on field programmable gate array (FPGA) technology is designed for the heterodyne interferometer, and it contributes to real-time display of electron density. To extract phase information, a novel numerical algorithm related to fast Fourier transform is written on the FPGA chip and enables one to obtain phase shift without being affected by amplitude variation induced by plasma absorption or frequency modulation from the outer electromagnetic environment. The interferometer achieves minimum measurable electron density in the order of 1016 m−3. With the plasma diagnosis, electron density and low frequency tearing mode have been measured during the first experimental campaign.